2017
DOI: 10.1667/rr14602.1
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based Metabolomics Analysis of Liver from C57BL/6 Mouse Exposed to Ionizing Radiation

Abstract: The effects of ionizing radiation to human health are of great concern in the field of space exploration and for patients considering radiotherapy. However, to date, the effect of high-dose radiation on metabolism in the liver has not been clearly defined. In this study, 1H nuclear magnetic resonance (NMR)-based metabolomics combined with multivariate data analysis was applied to study the changes of metabolism in the liver of C57BL/6 mouse after whole-body gamma (3.0 and 7.8 Gy) or proton (3.0 Gy) irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…In the last few years, many LC-MS metabolomics studies have identified many metabolites associated with radiation exposure 16,21 . However, there are few NMR based studies that have exploited the potential of metabolomics for the identification of potent metabolite markers [22][23][24][25] . Undoubtedly the sensitivity of LC-MS is way ahead of NMR for profiling but the ease of acquisition, identification of metabolites and reproducibility of information in spectrum makes NMR based metabolomics a suitable and comfortable platform in biomarker identification.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, many LC-MS metabolomics studies have identified many metabolites associated with radiation exposure 16,21 . However, there are few NMR based studies that have exploited the potential of metabolomics for the identification of potent metabolite markers [22][23][24][25] . Undoubtedly the sensitivity of LC-MS is way ahead of NMR for profiling but the ease of acquisition, identification of metabolites and reproducibility of information in spectrum makes NMR based metabolomics a suitable and comfortable platform in biomarker identification.…”
Section: Discussionmentioning
confidence: 99%
“…O-Phosphocholine acts as an intermediate in phosphatidylcholine synthesis, which is beneficial for memory loss, hepatitis, gallbladder disease, kidney disease, [60] and boosting the immune system. [61] Intake of betaine supplement is complimented with health benefits of improved performance and muscle endurance. [62,63] Besides, we also identified piperidine in pulp tissues with significantly high abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in accord with the results obtained in the present investigation, RT has been shown to increase the fecal content of α-ketobutyrate, valine, isoleucine, and alanine in cervical cancer patients [ 15 ]. RT also influenced the serum concentrations of 28 metabolites in patients with glyoma [ 16 ], increased the hepatic glutamine concentrations [ 17 ], and significantly modified the saliva metabolome [ 18 ] in mice. Taken together, these data suggest that RT does, indeed, influence metabolism in cancer patients.…”
Section: Discussionmentioning
confidence: 99%